Improving Satellite Multicast Security Scalability by Reducing Rekeying Requirements. - Hubenko, V.P (IEEE Network : the magazine of global information exchange)
As multicasting technologies grow in popularity, so does the need for scalable security architectures to support the user base. Significant research efforts are ongoing in the areas of group-key distribution and management. However, little research has addressed the security of very large, distributed groups communicating via low-earth orbit satellite networks. In this article, we review the requirements common to most secure, multicast networking environments; discuss existing scalable multicast security architectures; and present a novel modular scalable architecture for secure multicast, adapted to a low-earth orbit satellite system. Simulated results reveal a twelve-fold reduction in average user rekeying and an order of magnitude reduction in required key distribution versus the baseline architecture.